2023
DOI: 10.3390/foods12061165
|View full text |Cite
|
Sign up to set email alerts
|

Physical–Chemical and Sensory Quality of Oat Milk Produced Using Different Cultivars

Abstract: Oat milk, as an emerging plant-based milk substitute, has become popular in recent years. However, the stability and flavor of oat milk products are hindering their quality. The examination of the processing capacities of potential oat cultivars could help to improve product quality. In the present study, the properties of oat milk produced from one Australian and three Chinese cultivars were compared. The stability of oat milk produced using our manufacturing process was superior to the commercial product and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Current research on the composition of plant-based beverages has reported that the beverages are high in fat, carbohydrates and protein, which differ depending on the plant group from which they are derived. The soluble solids contents in samples formulated with oats, almonds and chestnuts were above 30 g/100 g, whereas, for samples formulated with coconut and soy, the values were below 30 g/100 g [ 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Current research on the composition of plant-based beverages has reported that the beverages are high in fat, carbohydrates and protein, which differ depending on the plant group from which they are derived. The soluble solids contents in samples formulated with oats, almonds and chestnuts were above 30 g/100 g, whereas, for samples formulated with coconut and soy, the values were below 30 g/100 g [ 58 , 59 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, it was found that compared with the other three oat cultivars, oat milk produced by Chinese Bayou 01 (ZBY01) had the most acceptability and quality. 58 Syed et al optimized the pretreatment process of oats with three different soaking times (1 h, 6 h, 8 h) at a 1 : 2.7 ratio of oats to water to produce oat milk, indi-…”
Section: Oat Raw Materials and Their Pretreatmentsmentioning
confidence: 99%
“…More recently, it was found that compared with the other three oat cultivars, oat milk produced by Chinese Bayou 01 (ZBY01) had the most acceptability and quality. 58 Syed et al optimized the pretreatment process of oats with three different soaking times (1 h, 6 h, 8 h) at a 1 : 2.7 ratio of oats to water to produce oat milk, indicating that oat soaked for 8 h had better quality and acceptability of oat milk. 19 65 g of unprocessed oat flakes was added to 250 mL of distilled water and soaked at 4 °C for 6 h to investigate its effect on the GI and a GI value of 38.6 was obtained for oat milk.…”
Section: Production Of Oat Milkmentioning
confidence: 99%
“…The "uses" category also mentioned a healthier alternative to milk. Oats are ideal milk alternatives addressing the problem of milk allergies, lactose intolerance, and celiac diseases [4,19,23]. The remaining categories with less than 5% of citations mentioned emotions (comfort, warm, enjoyable, satisfying); opinions (cost, newness of product); flavors (variants of oat milks and oat products); brands or locations (coffee shop brands, grocery locations); milk (terms relating to milk); and others.…”
Section: Free Word Analysismentioning
confidence: 99%
“…Most marketed beverages are fortified with antioxidants, vitamins, collagen, and protein [22] while limited studies have been conducted on β-glucan fortified plant-based milks. An oat variety with the highest β-glucan content showed a better oat milk flavor and appearance; however, further studies are still required [23].…”
Section: Introductionmentioning
confidence: 99%